2023
DOI: 10.2147/copd.s396311
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophils and Clinical Outcomes in Inpatients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Prospective Cohort Study

Abstract: Purpose The prognostic value of blood eosinophils in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) remains controversial. This study aimed to evaluate whether blood eosinophils could predict in-hospital mortality and other adverse outcomes in inpatients with AECOPD. Methods The patients hospitalized for AECOPD were prospectively enrolled from ten medical centers in China. Peripheral blood eosinophils were detected on admission, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies have indicated that patients with AECOPD with low blood eosinophils tend to be older, have more comorbidities and are more susceptible to severe bacterial infections, all of which contribute to poor prognoses. [36][37][38] Others regard eosinophilic AECOPD as an inflammatory phenotype, which demonstrates a favorable response to corticosteroid treatment. 10,13,14,[39][40][41] Our results align with this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that patients with AECOPD with low blood eosinophils tend to be older, have more comorbidities and are more susceptible to severe bacterial infections, all of which contribute to poor prognoses. [36][37][38] Others regard eosinophilic AECOPD as an inflammatory phenotype, which demonstrates a favorable response to corticosteroid treatment. 10,13,14,[39][40][41] Our results align with this perspective.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, the in-hospital mortality rates were slightly lower in China, which ranged from 1.4% to 10.1%. 22,23,28,[32][33][34][35] Pu et al conducted a prospective cohort study with 12831 AECOPD inpatients, and found that the in-hospital mortality rate was 1.4%. 32 Peng et al conducted a retrospective study with 6668 patients hospitalized for AECOPD, and reported that the in-hospital mortality was 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,28,[32][33][34][35] Pu et al conducted a prospective cohort study with 12831 AECOPD inpatients, and found that the in-hospital mortality rate was 1.4%. 32 Peng et al conducted a retrospective study with 6668 patients hospitalized for AECOPD, and reported that the in-hospital mortality was 1.9%. 33 Five other studies with relatively smaller samples reported inhospital mortality rates of 6.0%, 22 7.0%, 34 7.2%, 35 9.7%, 28 and 10.1%, 23 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, eosinophil levels in peripheral blood have become one of the emerging biomarkers in patients with COPD because there is evidence that eosinophils participate in the pathophysiological mechanisms of the disease, and their measurement is possible in most laboratories [ 11 ]. However, the effect of eosinophils in stable COPD and COPD exacerbations may differ [ 12 ].…”
Section: Introductionmentioning
confidence: 99%